Effect of anti microbial and ﬂuorescence on L-Alaninium maleate (LAM) macro and nano crystals - SenthilKannan, K.; Kaleemullah, Khan B.; Abdul Jaffar, Ali H.; Ponnusamy, Vinoth Kumar; Govindan, Natana Murugaraj (Elsevier Ltd, 2020)
The Fluorescence (FL) and Anti Microbial (AM) effects of the L-Alaninium maleate which is Zwitter ionic in nature is studied and reported, XRD data reveals that it is orthorhombic and space group as P212121 and of NLO with SHG type. The FL emission wavelength of LAM is 399 nm for macro scale and 403 nm, 406 nm, 430 nm for nano scales of 50 nm, 29 nm and 27 nm of sample sizes. The Anti microbial analysis is also studied for macro scale and for nano scales of LAM for 4 species such as Staphylococcus sp., Pseudomonas sp., E. coli sp., Klebsiella sp., respectively.